Gut microbiota influences pathological angiogenesis in obesity‐driven choroidal neovascularization - Elisabeth MMA Andriessen; Ariel M Wilson; Gaelle Mawambo; Agnieszka Dejda; Khalil Miloudi; Florian Sennlaub; Przemyslaw Sapieha (EMBO Molecular Medicine, 2016)
Abstract Age‐related macular degeneration in its neovascular form (NV AMD) is the leading cause of vision loss among adults above the age of 60. Epidemiological data suggest that in men, overall abdominal obesity is the second most important environmental risk factor after smoking for progression to late‐stage NV AMD. To date, the mechanisms that underscore this observation remain ill‐defined. Given the impact of high‐fat diets on gut microbiota, we investigated whether commensal microbes influence the evolution of AMD. Using mouse models of NV AMD, microbiotal transplants, and other paradigms that modify the gut microbiome, we uncoupled weight gain from confounding factors and demonstrate that high‐fat diets exacerbate choroidal neovascularization (CNV) by altering gut microbiota. Gut dysbiosis leads to heightened intestinal permeability and chronic low‐grade inflammation characteristic of inflammaging with elevated production of IL‐6, IL‐1β, TNF‐α, and VEGF‐A that ultimately aggravate pathological angiogenesis.